Research on Innovative Design of Takeaway Food Packaging Materials and Functions Under the Concept of Sustainable Development - Zhu, Lin (Journal of Ecohumanism, 2025)
In the context of global advocacy for sustainable development and the Sustainable Development Goals (SDGs), the rapid expansion of the takeaway industry has resulted in a significant increase in packaging waste. Traditional food packaging materials often fail to meet environmental standards, are functionally limited, and lack innovation. This research examines how to address the functional needs of takeaway food packaging while minimizing its negative environmental impact, emphasizing innovative solutions aligned with eco-humanism development principles. By analyzing the challenges, limitations, and functional requirements of existing Chinese takeaway packaging, the study proposes design solutions that integrate sustainable development principles. Utilizing methods such as literature analysis, case studies, market research, and material experimentation, the research explores the application of new eco-friendly materials and optimization of packaging multifunctionality. The findings aim to promote sustainable practices, enhance user experiences, and reduce environmental waste, thereby supporting the green transformation of the takeaway industry. This study provides practical insights for designers, businesses, and policymakers, fostering innovation and sustainable development within the packaging industry and aligning with broader environmental goals.